THE EFFECT OF INTELLECTUAL INTELLIGENCE, EMOTIONAL INTELLIGENCE, SPIRITUAL INTELLIGENCE AND UNDERSTANDING OF THE ACCOUNT PROFESSIONAL CODE OF CONDUCT ON THE ETHICAL BEHAVIOR OF ACCOUNTING STUDENTS AND THEIR IMPACT ON INTEREST TO BE A PUBLIC ACCOUNTANT - Asep Kurniawan; Ai Nuraisah (ACCRUALS (Accounting Research Journal of Sutaatmadja), 2022)
There are many differences in the results of research regarding the variables of intellectual intelligence, emotional intelligence, and spiritual intelligence on the ethical behavior of accounting students. The diversity of the results of these studies causes this research to be carried out again to obtain empirical evidence. Researchers are interested in conducting research with the title "The Effect of Intellectual Intelligence, Emotional Intelligence, Spiritual Intelligence and Understanding of the Code of Ethics of the Accounting Profession on the Ethical Behavior of Accounting Students and Their Impact on Interest in Becoming a Public Accountant". This study uses quantitative data types. Data collection techniques using questionnaires or questionnaires, questionnaires or questionnaires. In this study, there are three research variables, namely: (1) dependent variable: interest in becoming a public accountant (Z); (2) Intervening variables: ethical behavior of accounting students (Y), and (3) Independent variables: Intellectual Intelligence, Emotional Intelligence, Spiritual Intelligence and Understanding of Accountants' Code of Ethics. The tests carried out are validation and reliability tests. The data analysis method used is descriptive statistical analysis, classical assumption test, and hypothesis testing. The results of the analysis show that partial intellectual intelligence has a positive effect on the ethical behavior of accounting students. The results of the analysis show that partial emotional intelligence has no effect on the ethical behavior of accounting students. Partially, spiritual intelligence has a positive effect on the ethical behavior of accounting students. Partially, the variable understanding of the accountant's code of ethics has a positive effect on the ethical behavior of accounting students. Partially, the variables of intellectual intelligence (X1), emotional intelligence (X2), spiritual intelligence (X3), and understanding of the accountant's code of ethics (X4) simultaneously influence the ethical behavior of accounting students. The ethical behavior of accounting students has no effect on their interest in becoming a public accountant